2009
DOI: 10.1016/j.foreco.2009.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Windthrow and salvage logging in an old-growth hemlock-northern hardwoods forest

Abstract: Although the initial response to salvage (also known as, post-disturbance or sanitary) logging is known to vary among system components, little is known about longer term forest recovery. We examine forest overstory, understory, soil, and microtopographic response 25 years after a 1977 severe wind disturbance on the Flambeau River State Forest in Wisconsin, USA, a portion of which was salvage logged. Within this former old-growth hemlock-northern hardwoods forest, tree dominance has shifted from Eastern hemloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…Windthrow areas are usually cleared; harvesting of disturbed stands is practiced for the economic (recouping of the financial losses before wood-quality deterioration) and sanitary reasons (damaged trees can attract insects and consequently insects can attack undisturbed trees in their neighbourhood). Recently, there appeared studies discussing the impact of the post-disturbance logging as a combination of natural disturbance and subsequent harvesting on one side, and the impact of natural disturbance or clear-cutting alone on the other side (Lindenmeyer and Noss 2006;Lang et al 2009). As the authors emphasised, the main question is whether different management alters forest recovery, biodiversity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Windthrow areas are usually cleared; harvesting of disturbed stands is practiced for the economic (recouping of the financial losses before wood-quality deterioration) and sanitary reasons (damaged trees can attract insects and consequently insects can attack undisturbed trees in their neighbourhood). Recently, there appeared studies discussing the impact of the post-disturbance logging as a combination of natural disturbance and subsequent harvesting on one side, and the impact of natural disturbance or clear-cutting alone on the other side (Lindenmeyer and Noss 2006;Lang et al 2009). As the authors emphasised, the main question is whether different management alters forest recovery, biodiversity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…While there is clear evidence of the negative effects of salvaging on regeneration in some circumstances (e.g., large-scale high severity disturbance and salvaging - Donato et al 2006, Jonasova et al 2010), the evidence is less clear following a combination of intermediate severity disturbance and salvage logging (Peterson & Leach 2008a, Lang et al 2009, D'Amato et al 2011, Kramer et al 2014. It is important to note that we focused on the influence of salvage logging on vegetation in this study.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 92%
“…Peterson & Leach (2008a, 2008b they found clear differences in microsite diversity and abundance between the two treatments, the density and diversity of herbs and tree seedlings did not show a detrimental response to salvaging. Lang et al (2009) followed the long-term vegetation response to non-salvage and salvage treatments in a mixed forest damaged by severe wind in Wisconsin, USA. They found that the structure and composition of tree species on both treatments largely converged after 25 years, despite substantial damage to advance regeneration during salvage operations.…”
Section: Introductionmentioning
confidence: 99%
“…Wind disturbance usually does not facilitate the establishment of pioneer species, and late-successional species largely remain dominant [30][31][32]. Long-distance colonization by species of relatively low shade tolerance (e.g., Betula papyrifera Marsh., Populus tremuloides Michx., Pinus strobus L.) occurs primarily after fire.…”
Section: Model Descriptionmentioning
confidence: 99%